Implementing Open Government At The Local Level In Romania: Case Study: The Municipality Of Brașov - Matei-Sarandi, Ana-Maria (PT. Antis International Publisher, 2024)
Objective: With an emphasis on the use of digital platforms to advance open governance, this study attempts to assess how well Brașov City Hall's efforts in 2020–2024 foster two-way contact with the public. Method: The online resources used by Brașov City Hall were examined using a thorough case study methodology, which evaluated the openness of its public statements and the degree to which these tools support collaborative governance. Results: Citizens report unsolved issues and communication delays, showing deficiencies in two-way participation, and the findings show major gaps in responsiveness and openness. Novelty: By offering a thorough case study on Brașov's open government initiatives, this study adds to the body of material already in existence. It highlights how crucial it is to not just use digital tools but also make sure that public input successfully results in significant governance reforms. By emphasizing these factors, this study emphasizes how important it is for local governments to improve effective and transparent citizen participation in order to foster true collaborative governance and foster public trust.